2022
DOI: 10.3390/ijms232012372
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Collective Migration by Single-Cell Tracking Aimed at Understanding Cancer Metastasis

Abstract: Metastasis is a major complication of cancer treatments. Studies of the migratory behavior of cells are needed to investigate and control metastasis. Metastasis is based on the epithelial–mesenchymal transition, in which epithelial cells acquire mesenchymal properties and the ability to leave the population to invade other regions of the body. In collective migration, highly migratory “leader” cells are found at the front of the cell population, as well as cells that “follow” these leader cells. However, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Several biological assays, such as migration, proliferation, and cell-cycle assays, are based on single-cell time-lapse microscopy [14][15][16][17]. The reliability of such assays largely depends on the assay's ability to properly track each single cell over a stack of images.…”
Section: Introductionmentioning
confidence: 99%
“…Several biological assays, such as migration, proliferation, and cell-cycle assays, are based on single-cell time-lapse microscopy [14][15][16][17]. The reliability of such assays largely depends on the assay's ability to properly track each single cell over a stack of images.…”
Section: Introductionmentioning
confidence: 99%
“…Pathological observations show that malignant cancer cells frequently invade the surrounding normal tissue in collective rather than individual cell migration. 1 , 2 For individual cell migration, it has been found that the Rho/ROCK signaling is up-regulated and correlates with disease progression. 3 Meanwhile, Rho activates myosin-II and the actomyosin-mediated contraction creates tension within the cells.…”
mentioning
confidence: 99%